PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT.TANIMAS SOAP INDUSTRIES (PERUSAHAAN MANUFAKTUR DAN EKSPORTIR SABUN) - Gold win; Cut Fitri Rostina; Hendra Nazmi; Mei lissa; Eiklecia Ventriani U Zebua (Universitas Islam Islam Sumatera Utara, 2019)
This study aims to determine the effect of job satisfaction and work motivation on employee performance at PT. Tanimas Soap Industries. This research is survey research. PT. Tanimas Soap Industries is a company engaged in manufacturing and exporting soap. The researcher used simple random sampling technique using the help of Slovin formula. With a population of129 people and an error rate(e) of 5%, the sample(n) of this study was 97 people while the validity and reliability tests were taken from the rest of the population after calculating Slovin formula as many as 30 people. The data analysis model used is multiple linear regression using SPSS v.17.0 software. From this research, Reseacher got a result that tcount ttable work satisfaction variable (3,703 1,985) with significance 0,000 0,05 and tcount ttable work motivation variable (3,814 1,985) with significance 0,000 0,05 and Fcount Ftable was24,750 3,09 with significance 0,000 0,05. Job satisfaction has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance and job satisfaction and work motivation have an effect simultaneously on employee performance.